Modulating the strength of hydrogen bond acceptors to achieve low Caco2 efflux for oral bioavailability of PARP inhibitors blocking centrosome clustering. Issue 19 (1st October 2016) - Gu, Chungang; Lamb, Michelle L.; Johannes, Jeffrey W.; Sylvester, Mark A.; Eisman, Mark S.; Harrison, Rane A.; Hu, Haiqing; Kazmirski, Steven; Mikule, Keith; Peng, Bo; Su, Nancy; Wang, Wenxian; et al.
Graphical abstract: Abstract: During the lead generation and optimization of PARP inhibitors blocking centrosome clustering, it was discovered that increasing hydrogen bond acceptor (HBA) strength improved cellular potency but led to elevated Caco2 and MDR1 efflux and thus poor oral bioavailability. Conversely, compounds with lower efflux had reduced potency. The project team was able to improve the bioavailability by reducing efflux through systematic modifications to the strength of the HBA by changing the electronic properties of neighboring groups, whilst maintaining sufficient acceptor strength for potency. Additionally, it was observed that enantiomers with different potency showed similar efflux, which is consistent with the promiscuity of efflux transporters. Eventually, a balance between potency and low efflux was achieved for a set of lead compounds with good bioavailability which allowed the project to progress towards establishing in vivo pharmacokinetic/pharmacodynamic relationships.